2019
DOI: 10.3390/ijerph16245000
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Papillomavirus (HPV) and Other Sexually Transmitted Infections (STIs) among Italian Women Referred for a Colposcopy

Abstract: Sexually transmitted infections (STIs) represent a major cause of morbidity in women and men worldwide. Human Papillomavirus (HPV) infections are among the most prevalent STIs and persistent infections with high-risk HPV (hrHPV) genotypes can cause cervical dysplasia and invasive cervical cancer. The association of other STIs with HPV cervical infection and/or dysplasia has however not yet been fully elucidated. The aim of this study was to assess the prevalence of HPV and other STIs among women presenting wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…Marianna Martinelli et al also evaluated some of STI pathogens in women Pap smear with an abnormal cervical cytology and reported prevalence of 6(5.26%), 2(1.75%), 0(0%) and 0(0%) in U. urealyticum, M. hominis, C. trachomatis and N. gonorrhoeae respectively in high-risk HPVs (31). The prevalence of U. urealyticum, M. hominis, C. trachomatis and N. gonorrhoeae in our study was higher (25.8%, 12.9%, 3.2%, 6.4% respectively) in high-risk HPV group, as compared with the study conducted by Marianna Martinelli.…”
Section: Discussionmentioning
confidence: 99%
“…Marianna Martinelli et al also evaluated some of STI pathogens in women Pap smear with an abnormal cervical cytology and reported prevalence of 6(5.26%), 2(1.75%), 0(0%) and 0(0%) in U. urealyticum, M. hominis, C. trachomatis and N. gonorrhoeae respectively in high-risk HPVs (31). The prevalence of U. urealyticum, M. hominis, C. trachomatis and N. gonorrhoeae in our study was higher (25.8%, 12.9%, 3.2%, 6.4% respectively) in high-risk HPV group, as compared with the study conducted by Marianna Martinelli.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between high-risk HPV (hrHPV) infections and other pathogens could accelerate cancer progression, enhancing HPV replication and persistence of infection. A high prevalence of STIs has also recently been reported in Italy in association with hrHPV and cervical dysplasia [ 8 ]. Wang and colleagues reported an association between Ureaplasma urealyticum (UU) subtypes and cervical cancer [ 7 ]; further studies reported that Chlamydia trachomatis (CT) increases the risk of cervical cancer [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been estimated that 25% of all sexually active female adolescents have experienced one or more forms of sexually transmitted infection, with the most common as human papillomavirus and Chlamydia trachomatis . Sexually transmitted infections have established as major cause of morbidity among women and men that has potential for high risk human papillomavirus (hrHPV) infections which in chain-like reaction could spur cervical cancer [ 13 ]. While the identification of STIs as co-factor of cervical cancer in most women that are HPV-positive (Martinelli et al [ 13 ]) cannot be treated with levity, the evidence of similar linkage betweenSTD trichomoniasis and prostate cancer [ 14 ] should call for serious concern in public health domain.…”
Section: Introductionmentioning
confidence: 99%